Chemical Composition and Sensory Characteristics of Skimmed Milk Kefir Sensory on Variation of Concentration of Light Coconut Extract (Cocos Nucifera L.) - Yoakhim Yafet Engelhard Oessoe; Lucia Cecilia Mandey; Cecillia Angela Fernandez (Postgraduate, University of Mataram, 2024)
Kefir is a fermented milk product that is processed through fermentation of kefir granules. The objectives of this study are: 1. To analyse the effect of young coconut extract concentration on total microbes, ethanol and pH value of skimmed milk kefir. 2. To analyse the sensory test results of skimmed milk kefir with young coconut extract concentration. The method used in this research is Completely Randomised Design (CRD) with the treatment of variations in the percentage of skimmed milk and young coconut extract, namely: 100% skimmed milk: 0% young coconut extract; 95% skimmed milk: 5% young coconut extract; 90% skimmed milk: 10% young coconut extract; 85% skimmed milk: 15% young coconut extract; 80% skimmed milk: 20% young coconut extract with 3 repetitions and obtained 15 experimental units. The data obtained were analysed by ANOVA (Analysis of Variant). The results showed that increasing the concentration of young coconut extract increased the total number of microbes. Total microbes ranged from 1.48 x 10⁸ to 2.17 x 10¹⁰. Increasing the extract concentration from 15% to 20% increased the alcohol content from 0.07% to 0.20. Increasing the concentration of young coconut extract also significantly decreased the pH value of kefir after fermentation, with the lowest pH value (3.18) at 20% concentration. The concentration of young coconut extract in skimmed milk kefir significantly affected colour, texture and taste.